2011
DOI: 10.1007/s13149-010-0119-z
|View full text |Cite
|
Sign up to set email alerts
|

Séroépidémiologie de la rubéole, de la varicelle et des infections par le cytomégalovirus et le parvovirus B19 chez les femmes enceintes dans la région de Sousse, Tunisie

Abstract: The aim of the study is to evaluate seroprevalence of rubella virus (RV), cytomegalovirus (CMV), varicella zoster virus (VZV), and parvovirus B19 (PB19) in 404 Tunisian pregnant women, and to determine reliability of maternal past history of eruption. Sociodemographic characteristics, risk factors, and past history of eruption were collected through a questionnaire. Serologic tests were performed using enzyme immunoassays. Risk factors were analyzed using univariate and multivariate logistic regression models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 26 publications
(35 reference statements)
4
6
0
Order By: Relevance
“…The seroprevalence of HCMV IgG among pregnant Palestinian women and children as presented here is comparable to regional studies from Egypt [ 36 ], Qatar [ 30 ], Tunisia [ 37 ], Bahrain [ 38 ], Iraq [ 39 ], Iran [ 4 ],Turkey [ 28 ], [ 29 ]) and ranks among countries with high seroprevalence, comparable to Brazil, Cuba, Japan and Taiwan [ 24 - 27 , 40 , 41 ]. Lower regional seroprevalence is reported from Sudan at a rate of 72% among pregnant women [ 42 ] and Syria at a rate of 74.5% among college female students [ 43 ].…”
Section: Discussionsupporting
confidence: 84%
“…The seroprevalence of HCMV IgG among pregnant Palestinian women and children as presented here is comparable to regional studies from Egypt [ 36 ], Qatar [ 30 ], Tunisia [ 37 ], Bahrain [ 38 ], Iraq [ 39 ], Iran [ 4 ],Turkey [ 28 ], [ 29 ]) and ranks among countries with high seroprevalence, comparable to Brazil, Cuba, Japan and Taiwan [ 24 - 27 , 40 , 41 ]. Lower regional seroprevalence is reported from Sudan at a rate of 72% among pregnant women [ 42 ] and Syria at a rate of 74.5% among college female students [ 43 ].…”
Section: Discussionsupporting
confidence: 84%
“…The seroprevalence of HCMV IgG in pregnant women in this study (97.55%) was comparable to a regional study carried out in the KPK province of Pakistan [ 21 ] as well as other countries such as Qatar [ 22 ], Egypt [ 23 ], Tunisia [ 24 ], Iraq [ 25 ], Iran [ 26 ], Brazil [ 27 ] and Turkey [ 28 ]. All these studies have reported higher seroprevalence rates than developed countries such as the United Kingdom [ 24 ] and Germany [ 29 ].…”
Section: Discussionsupporting
confidence: 83%
“…However, other studies showed higher rate than result of present study, which reported a detection rates ranged between 62.3% and 81.1% (19,20) . When compare to studies conducted in Arabic countries such as Tunisia, where a 96.3% seroprevalence of HCMV antibody was reported among 404 Tunisian pregnant women (21) . High frequency rate could therefore be related to a higher risk of infection, but it may also be related to use less sensitive diagnostic methods such as virus culture in certain areas compare with other technique.…”
Section: Discussionmentioning
confidence: 60%